Rescue and Conservation of Male Adult Alpacas (Vicugna pacos) Based on Spermatogonial Stem Cell Biotechnology Using Atomized Black Maca as a Supplement of Cryopreservation Medium - Valdivia, Martha; Bravo, Zezé; Reyes, Jhakelin; Gonzales, Gustavo F. (Frontiers in Veterinary Science, 2021)
This is the first time that testicular tissue (n = 44) and isolated testicular cells (n = 51) were cryopreserved from alpaca testes 24 h postmortem. For this purpose, internally designed freezing media and cryopreservation protocols were used. Testicular tissue fragments (25 mg) and isolated testicular cells were frozen in MTDB (trehalose and black maca), MTD (trehalose), MSDB (sucrose and black maca), and MSD (sucrose) media. Isolated spermatogonial cells were cryopreserved in two ways, before and after proliferation in vitro. After cryopreservation, the percentage of cell viability in Group 1 (>50% of cell viability) by trypan blue did not show differences within each group (p > 0.05) but showed significant differences when comparing fragments with isolated cells (p < 0.05). Spermatogonial stem cells (SSC) were identified by flow cytometry as strong Dolichos biflorus agglutinin (sDBA) and mitochondrial activity of SSC as strongly positive for MitoSense (sMitoSense+) in intact mitochondria cells, weakly positive for MitoSense (wMitoSense+) in early apoptosis, and necrosis with 7-Aminoactinomycin-D positive (7-AAD). After freezing, in Group 1M (≥30% sMitoSense+), the fragments did not show differences between the media (p > 0.05), but in the isolated cells frozen in MSDB medium, 63.68 ± 8.90% (p < 0.05). In Group 2M (<30% sMitoSense+), necrosis (7AAD+) in MSDB medium was 27.03 ± 5.80%, and necrosis in isolated cells was 14.05 ± 9.3% with significant differences between these groups (p < 0.05); in sMitoSense+, the isolated cells (34.40 ± 23%) had a higher percentage than the fragments (12.4 ± 5.2) (p < 0.05). On the other hand, MSDB and MSD media were significantly higher for isolated cells than for fragments in sDBA+ (p < 0.05). On the other hand, the SSC (sDBA+) had significant differences (p < 0.05) between fresh cells 7.43 ± 1.3% (sDBA+) compared with those cryopreserved in MSDB medium 1.46 ± 0.34% (sDBA+). Additionally, the proliferated and cryopreserved SSC 6.29 ± 1.17% (sDBA+) did not show significant differences concerning the fresh cells (p > 0.05). In conclusion, the black maca showed antioxidant properties when it was included in the freezing medium and, therefore, improved the SSC's conservation of the alpaca. Furthermore, the proliferation of isolated cells in vitro produces a higher amount of SSC after thawing them for further preclinical or clinical work.